Shot blasting abrasives
Patent Information
- Application Number
- JP2021016228
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-04
- Publication Date
- 2025-03-06
- Estimated Expiration
- 2041-02-04
AI Technical Summary
【0013】 本発明に係るショットブラスト用研掃材によれば、処理対象物の表面仕上げをミクロンレベルまで均一化することが可能となる。また、優れた耐久性が得られる。
Smart Images

Figure 0007641127000002 
Figure 0007641127000003 
Figure 0007641127000004
Abstract
Description
[Technical field]
[0001] The present invention relates to an abrasive for shot blasting. [Background technology]
[0002] Blasting (polishing, cleaning), a surface treatment method, is a technique in which spherical or abrasive blasting materials (metals, ceramics, etc.) are sprayed at high speed onto the object to be treated using an air blasting method (compressed air) or an impeller method (centrifugal force projection), modifying the surface. The purposes of blasting are diverse, including rust removal, cleaning the base material, activation, roughening, and peening effects. Types of blasting materials (abrasives) include shot blasting, which is a spherical steel ball called steel shot, and grid blasting, which is made of grains with many sharp edges.
[0003] Patent Document 1 proposes using reduced iron powder having an apparent density within a specified range as a shot blasting material for surface finishing, thereby preventing unevenness in the surface finishing process while providing an appropriate abrasive force. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2016-69708 A Summary of the Invention [Problem to be solved by the invention]
[0005] In recent years, there has been a demand for more uniform surface finishing (e.g., roughening) of objects such as aluminum substrates by shot blasting. Specifically, there is a demand for the surface roughness (Ra) of the objects to be treated to be uniform to the micron level. There is also a demand for further improvement in the durability of abrasives.
[0006] SUMMARY OF THE PRESENT EMBODIMENT An object of the present invention is to provide an abrasive for shot blasting which is capable of uniformly finishing the surface of an object to be treated down to the micron level and which is highly durable. [Means for solving the problem]
[0007] The abrasive for shot blasting according to the present invention, which achieves the above object, has an apparent density of 3.0 g / cm 3 More than 4.0g / cm 3 The BET specific surface area is 0.10 m 2 / g or more 0.50m 2 / g or less.
[0008] By having the apparent density in the above range, the desired polishing power can be obtained and the surface finish can be uniformed. Also, by having the BET specific surface area in the above range, the stress during the impact due to the shot blasting treatment can be equalized, the surface finish can be uniformed, and the generation of fine powder of the abrasive due to the shot blasting treatment can be suppressed, improving durability.
[0009] In the abrasive material for shot blasting having the above-mentioned structure, it is preferable that the Vickers hardness is in the range of 250 HV or more and 300 HV or less.
[0010] In the abrasive for shot blasting having the above-mentioned structure, the content of metallic iron in the abrasive is preferably in the range of 94% by mass or more and 97% by mass or less.
[0011] In the abrasive material for shot blasting having the above-mentioned configuration, the carbon content in the abrasive material is preferably in the range of 0.002% by mass or more and 0.10% by mass or less.
[0012] In this specification, the "apparent density," "BET specific surface area," "Vickers hardness," "metallic iron content," "carbon content," and "volume average particle size" are values obtained by the measurement methods described in the examples below. Effect of the Invention
[0013] The abrasive cleaning material for shot blasting according to the present invention makes it possible to uniformly finish the surface of the object to be treated to the micron level, and also provides excellent durability. [Brief description of the drawings]
[0014] [Figure 1] 1 is a SEM photograph (magnification: 200 times) of the abrasive of Example 1. [Diagram 2] 1 is a SEM photograph (magnification: 200 times) of the abrasive of Example 4. [Diagram 3] 1 is a SEM photograph (magnification: 200 times) of the abrasive of Comparative Example 1. [Figure 4] 1 is a SEM photograph (magnification: 200 times) of the abrasive of Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] One of the major features of the shot blasting abrasive material according to the present invention (hereinafter, sometimes simply referred to as "abrasive material") is that it has an apparent density of 3.0 g / cm 3 More than 4.0g / cm 3 The apparent density of the abrasive is 3.0 g / cm or less. 3 If the apparent density of the abrasive is less than 4.0 g / cm, the magnitude of the impact stress on the surface of the object to be treated during shot blasting will vary, causing uneven treatment. Also, the abrasive will crack or chip with use, reducing its durability. On the other hand, if the apparent density of the abrasive is less than 4.0 g / cm, 3 If the density exceeds 100%, the productivity and yield of the abrasive will be significantly reduced. The more preferable range of the apparent density of the abrasive is 3.3 g / cm 3 More than 3.7g / cm 3 The range is as follows:
[0016] Another feature of the abrasive of the present invention is that the BET specific surface area is 0.10 m 2 / g or more 0.50m 2 The BET specific surface area of the abrasive is 0.10 m 2 If the BET specific surface area of the abrasive is less than 0.50 m / g, the magnitude of the impact stress on the surface of the object to be treated will vary, causing uneven treatment.2 If the BET specific surface area of the abrasive exceeds 0.15 m / g, the abrasive is more likely to crack or chip. 2 / g or more 0.30m 2 / g or less.
[0017] The Vickers hardness of the abrasive material according to the present invention is preferably in the range of 250HV to 300HV. If the Vickers hardness of the abrasive material is less than 250HV, the magnitude of the impact stress on the surface of the object to be treated during shot blasting may vary, resulting in uneven treatment. There is also a risk of the abrasive material cracking or chipping during use. On the other hand, if the Vickers hardness of the abrasive material exceeds 300HV, the surface roughness of the object to be treated may increase, resulting in uneven treatment. The more preferred range of the Vickers hardness of the abrasive material is in the range of 260HV to 280HV.
[0018] The metallic iron content of the abrasive according to the present invention is preferably in the range of 94% by mass to 97% by mass. By setting the metallic iron content of the abrasive in the above range, high durability of the abrasive and suppression of processing unevenness are achieved.
[0019] The carbon content of the abrasive according to the present invention is preferably in the range of 0.002% by mass or more and 0.10% by mass or less. By setting the carbon content of the abrasive in the above range, the abrasive has high durability and prevents uneven processing. The carbon content of the abrasive is more preferably in the range of 0.01% by mass or more and 0.10% by mass or less.
[0020] The volume average particle diameter D of the abrasive according to the present invention 50 The volume average particle diameter D of the abrasive is preferably in the range of 120 μm to 150 μm. 50 The range is 125 μm or more and 150 μm or less.
[0021] The materials to be shot blasted using the abrasive of the present invention include metals, ceramics, glass, plastics, rubber, etc. Among these materials, the abrasive of the present invention is preferably used for metal materials, and more preferably used for aluminum and aluminum alloys.
[0022] The material of the abrasive according to the present invention is not particularly limited as long as the apparent density and BET specific surface area satisfy the ranges specified by the present invention, but sponge iron powder produced by reducing iron oxide such as mill scale is preferable. The abrasive made of sponge iron powder is produced, for example, as follows.
[0023] (Method of manufacturing abrasives) Although there is no particular limitation on the method for producing the abrasive according to the present invention, the production method described below is preferred.
[0024] First, iron oxide with few impurities such as mill scale generated in the hot rolling process of a steelworks is introduced into a baking furnace such as a tunnel furnace together with a reducing agent and reduced to obtain sponge iron cake. The reduction method can be a known method described in JP-A-61-183402, JP-A-2005-264302, JP-A-2004-60000, etc. Carbon materials such as coke powder and coal can be used as the reducing agent.
[0025] Next, the sponge iron cake is crushed and pulverized to obtain sponge iron powder having a particle size of 500 μm or less. The crushing and pulverization processes can be performed using known devices and methods. The sponge iron powder obtained is sieved to remove particles having a particle size of more than 300 μm and less than 180 μm to obtain the first raw powder of the abrasive.
[0026] In addition, sponge iron cake is obtained in the same manner as the first raw powder, and then the sponge iron cake is crushed, pulverized, and sieved to obtain sponge iron powder having a particle size of more than 300 μm. This is called the second raw powder. The particle size of more than 300 μm is the sieve residue of the 300 μm sieve.
[0027] The second raw material powder may have a particle size of more than 300 μm, but the maximum particle size is preferably 500 μm. If the particle size of the second raw material powder is too large, it will affect the abrasive power when used as an abrasive. The BET specific surface area of the abrasive can be adjusted by adjusting the maximum diameter and the amount of the second raw material powder mixed. The BET specific surface area of the abrasive can also be adjusted by the time and intensity of the grinding and polishing processes described below.
[0028] The second raw material powder may be separated from the coarse particles generated in the crushing process of the first raw material powder. When the same operation is repeated multiple times, the second raw material powder may be separated from the coarse particles generated in the previous crushing process of the first raw material powder. For example, when the processing unit is lot-managed, the second raw material powder separated from the previous or previous-previous lot is used. The second raw material powder can be separated from particles with a particle size of over 300 μm by sieving, and multiple lots of the second raw material powder may be mixed and used depending on the amount to be added.
[0029] Next, the first raw material powder and the second raw material powder are mixed so that the second raw material powder is 20% by mass to 35% by mass relative to the first raw material powder to prepare a raw material for the abrasive. The BET specific surface area of the produced abrasive is adjusted by the mixing ratio of the second raw material powder.
[0030] The raw material for the abrasive is simultaneously crushed and polished in a Novo rotor mill. In the case of crushing using a conventional hammer mill, the impact of the crushing is large, and the sea-like structure on the surface of the raw material for the abrasive (iron powder) tends to collapse, resulting in a smaller particle size. In contrast, in the process using the Novo rotor mill, the rotor is rotated and polishing is performed by contact between the raw material particles, which prevents the particle size from becoming smaller and makes it possible to increase the apparent density. In addition, by attaching a screen with the desired opening size to the Novo rotor mill as necessary, the dust concentration inside the Novo rotor mill can be adjusted, enabling efficient crushing.
[0031] In addition, in the conventional method (disclosed in JP 2016-69708 A), raw materials of only one type of particle size (200 μm to 300 μm) were used, so the raw materials were easily crushed, and the amount of fine powder (for example, particle size 106 μm or less) generated during the crushing process was large, resulting in poor productivity. In contrast, in this manufacturing method, in which the first raw material powder is mixed with the second raw material powder, which is coarser than the first raw material powder, the sea of raw material powder (iron powder) is cotton The granular structure is less likely to collapse, making it possible to efficiently produce an abrasive having a high apparent density and a desired BET specific surface area.
[0032] In addition, even when using raw material of one type of particle size as in the conventional method, or when mixing a second raw material powder that is finer than the first raw material powder, it is possible to polish the surface of the raw material particles by using, for example, a cutter mill as a grinding device, and since the grinding strength is weaker than that of a noborotor mill, it is possible to increase the apparent density while suppressing the raw material particle size from becoming smaller.
[0033] The pulverization and polishing treatments using the Novo rotor mill may be repeated until the apparent density of the treated abrasive is reached as desired. After the treatment, the particle size distribution of the abrasive may be adjusted using a sieve or a cyclone, if necessary, depending on the intended use. For example, the particle size may be adjusted to 180 μm to 425 μm, 150 μm to 300 μm, 125 μm to 250 μm, 106 μm to 180 μm, or 75 μm to 150 μm. The pulverization and polishing treatments may be performed using separate processing equipment. EXAMPLES
[0034] Example 1 (Preparation of the first raw powder) The mill scale (iron oxide) used as the raw material was dried at 120°C in a rotary dryer, and then anthracite was added and mixed as a reducing agent. The anthracite used had a fixed carbon content of 80-90% and a size of 4 mm or less. In addition to the mixture of the mill scale and anthracite, coke powder with a fixed carbon content of 50-90% was prepared.
[0035] A mixture of mill scale and anthracite was filled into a silicon carbide heat-resistant container in a cylindrical shape, and coke powder was filled in the center and outside.The heat-resistant container was then subjected to reduction treatment in an air atmosphere in a tunnel kiln furnace at a temperature range of 1050℃ to 1250℃ to obtain sponge iron cake.
[0036] The sponge iron cake obtained by the above reduction treatment was pulverized in the following order to obtain a first raw material powder. (1) Crushing the material roughly to particle sizes of approximately 30 cm or less using a roll crusher (2) The hammer crusher crushes the material into particles of approximately 4 cm or less. (3) Coarsely crush the material into particles of approximately 4 mm or less using a hammer mill. (4) Finely grind the particles to a particle size of 500 μm or less using a Novo rotor mill. (5) By sieving, particles with a particle size of more than 300 μm and less than 180 μm are removed.
[0037] (Preparation of the second raw powder) A sponge iron cake was obtained in the same manner as for the first raw material powder, and then the sponge iron cake was crushed and pulverized to obtain a second raw material powder having a particle size of more than 300 μm.
[0038] (Production of raw materials for abrasives) The second raw material powder was added to the first raw material powder in an amount of 25 mass % to prepare a raw material for the abrasive.
[0039] (Crushing and grinding) The prepared raw material for the abrasive was simultaneously crushed and polished by a Novo rotor mill. The apparent density of the raw material for the abrasive after a predetermined period of processing was measured and found to be 3.0 g / cm. 3 ~4.0g / cm 3 This was repeated until the range The above-mentioned abrasive with an adjusted apparent density was classified in a cyclone with a classification point of 10 μm, and then particles with a particle size of 180 μm or more were removed using a vibrating sieve to obtain the abrasive according to Example 1. The composition and powder characteristics of the obtained abrasive were measured by the following method. The measurement results are shown in Table 1. Also, an SEM photograph (magnification 200 times) of the abrasive is shown in Figure 1.
[0040] (composition analysis) (Total Iron (T.Fe)) The total iron content (T.Fe) was measured according to JIS M8212.
[0041] (Metallic iron (M.Fe)) The amount of metallic iron in the sample was measured in accordance with JIS M8713-1993 "Reduction test method for iron ores", Reference 6.1 Metallic iron determination method, by stirring the sample in a bromine-methanol solution, extracting and dissolving the metallic iron, and titrating it with the chelate using an automatic potentiometric titrator.
[0042] (Carbon (C), Sulfur (S)) Carbon and sulfur were calculated using a carbon-sulfur analyzer (LECO CS-744).
[0043] (Oxygen (O)) The oxygen in the samples was calculated using an oxygen / nitrogen analyzer (TCH600, manufactured by LECO).
[0044] (apparent density) The apparent density of the abrasive was measured according to the procedure of the test method for apparent density of metal powder in "JIS Z 2504".
[0045] (BET specific surface area) The BET specific surface area of the abrasive was measured using a BET single point specific surface area measuring device (Macsorb HM model-1208, manufactured by Mountec Co., Ltd.) Specifically, 5,000 g of the sample was weighed out and filled into a standard cell with a diameter of 12 mm, and the sample was degassed at 200°C for 30 minutes before measurement.
[0046] (Particle size distribution: sieving) The particle size distribution of the abrasive was measured by sieving using the method specified in JIS Z 8815. The particle size is determined by the opening of the sieve.
[0047] (Particle size distribution: Laser diffraction particle size distribution analyzer MT) Particle size distribution of abrasives (D 10 ,D 50 ,D 90 ) was measured using a laser diffraction particle size distribution analyzer MT (Microtrac Model 9320-X100 manufactured by Nikkiso Co., Ltd.). The measurement was performed using the cumulative 10% particle size D 10 (μm), cumulative 50% average particle diameter D50 (μm), cumulative 90% particle size D 90 The value of was obtained.
[0048] (Vickers hardness) The Vickers hardness of the abrasives was measured by adding the abrasives to a resin, hardening it, polishing the surface with a rotary polisher, and then precipitating the cross section, and then using a nanoindenter (Elionix "ENT1100-b"). The measurement conditions for the nanoindenter were load-unload test mode, room temperature, and a load of 25 mmN.
[0049] (true density) The measurement was carried out using a true density measuring device (MICROMERITICS Accupic II 1340 series).
[0050] (Processing unevenness evaluation) Using a shot blasting tester (air blasting method), the abrasive was projected at a rate of approximately 17 g / sec at an air pressure of 0.28 MPa onto the object to be treated (aluminum substrate; A6063). The average value Avg of the surface roughness (arithmetic mean height Ra, root mean square height Rq, maximum height Rz) of the object to be treated after shot blasting was measured, and the coefficient of variation CV was calculated. The smaller the coefficient of variation, the less uneven the treatment.
[0051] (Durability evaluation) Using an Ervin test machine (manufactured by ERVIN), the abrasive was collided 500 times against carbon steel at an impeller speed of 5000 rpm. The particle size distribution of the abrasive after the collision was measured, and the increase in the amount of fine powder with a particle size of 106 μm or less was calculated using the following formula (1). The smaller the increase in the amount of fine powder after the Ervin test, the more durable the abrasive is evaluated to be. Increase rate of fine powder with a particle size of 106 μm or less (wt%) = (BA) / A × 100 (1) A: Mass ratio of particle size of 106 μm or less before durability evaluation B: Mass ratio of particle size of 106 μm or less after durability evaluation
[0052] Example 2 An abrasive was prepared in the same manner as in Example 1, except that only the first raw material powder was used and the equipment used in the pulverization and polishing processes was changed to a cutter mill system. The composition and powder characteristics of the prepared abrasive were measured in the same manner as in Example 1. The measurement results are shown in Table 1. Also, an SEM photograph (magnification 200 times) of the abrasive is shown in Figure 2.
[0053] Example 3 The first raw material powder was sieved using a sieve with an opening of 217 μm, and the raw material powder was made from powder having a particle size of 217 μm or less. An abrasive was prepared in the same manner as in Example 4. The composition and powder characteristics of the prepared abrasive were measured in the same manner as in Example 1. The measurement results are shown in Table 1.
[0054] Comparative Example 1 As in Example 1, 25% by mass of the second raw material powder was added to the first raw material powder to prepare a raw material for the abrasive cleaning material. Then, without carrying out a crushing process or a polishing process, particles with a particle size of 180 μm or more were removed from the raw material for the abrasive cleaning material using a vibrating sieve to prepare the abrasive cleaning material. The composition and powder characteristics of this abrasive cleaning material were measured in the same manner as in Example 1. The measurement results are shown in Table 1. Also, an SEM photograph (magnification 200 times) of the abrasive cleaning material is shown in FIG. 3.
[0055] Comparative Example 2 (Preparation of the first raw powder) The mill scale (iron oxide) used as the raw material was dried at 120°C in a rotary dryer, and then anthracite was added and mixed as a reducing agent. The anthracite used had a fixed carbon content of 80-90% and a size of 4 mm or less. In addition to the mixture of the mill scale and anthracite, coke powder with a fixed carbon content of 50-90% was prepared.
[0056] A mixture of mill scale and anthracite was filled into a silicon carbide heat-resistant container in a cylindrical shape, and coke powder was filled in the center and outside.The heat-resistant container was then subjected to primary reduction treatment in a tunnel kiln furnace at a temperature range of 1050℃ to 1250℃ in air, to obtain a primary reduced sponge iron cake.
[0057] The sponge iron cake obtained by the above-mentioned primary reduction treatment was subjected to secondary reduction treatment using a belt furnace and ammonia decomposition gas as atmospheric control at 900°C to obtain a secondary reduced sponge iron cake. Next, this secondary reduced sponge iron cake was disintegrated in a hammer mill to obtain a first raw material powder.
[0058] The first raw material powder thus prepared was used as a raw material for the abrasive. Then, without carrying out pulverization and polishing, particles with a particle size of 180 μm or more were removed from the raw material for the abrasive using a vibrating sieve to obtain the abrasive. The composition and powder characteristics of this abrasive were measured in the same manner as in Example 1. The measurement results are shown in Table 1. Also, FIG. 4 shows an SEM photograph (magnification 200 times) of the abrasive.
[0059] [Table 1]
[0060] As is clear from Table 1, the apparent density is 3.43 g / cm 3 ~3.63g / cm 3 , BET specific surface area is 0.17m 2 / g~0.23m 2 The abrasives of Examples 1 to 3, which are within the range of the present invention, have an apparent density of 2.64 g / cm 3 The abrasive of Comparative Example 1, which is smaller than the range specified in the present invention, and the apparent density of 2.61 g / cm 3 , BET specific surface area is 0.09m 2 The coefficient of variation CV of the surface roughness (arithmetic mean height Ra, root mean square height Rq, maximum height Ra) of the treated object was significantly smaller than that of the abrasive of Comparative Example 2, which was smaller than the range specified in the present invention. That is, the abrasives of Examples 1 to 3 had smaller treatment unevenness than the abrasives of Comparative Examples 1 and 2.
[0061] Furthermore, the abrasives of Examples 1 to 3 had a smaller increase in fine powder with a particle size of 106 μm or less after the Irvine test than the abrasives of Comparative Examples 1 and 2, and were therefore superior in durability. [Industrial Applicability]
[0062] The abrasive cleaning material for shot blasting according to the present invention makes it possible to uniformly finish the surface of the object to be treated down to the micron level, and also provides excellent durability.
Claims
1. An abrasive for use in shot blasting, Apparent density 3.0 g / cm 3 4.0g / cm or more 3 is as follows: BET specific surface area is 0.15m 2 / g or more 0.30m 2 / g or less, Vickers hardness is in the range of 260HV to 280HV.
1. A shot blasting abrasive cleaning material comprising:
2. 2. The abrasive for shot blasting according to claim 1, wherein the content of metallic iron in the abrasive is in the range of 94% by mass to 97% by mass.
3. 3. The abrasive for shot blasting according to claim 1, wherein the carbon content in the abrasive is in the range of 0.002% by mass or more and 0.10% by mass or less.
Citation Information
Patent Citations
Shotsutono funmatsuchokusetsuseizoho
JP1976106293A
Steel shot
JP1982009855A
Cut wire type iron system shot for blast
JP2000167772A
Iron powder for surface finishing and method for producing the same
JP2016069708A
Method for enhancing the rust resistance and the surface finish of a non-ferrous workpiece
US5512006A